Stimuli-responsive doxorubicin-loading Zr-MOF film for time-ordered tumor therapy and bone regeneration. (1st February 2023) - Yan, Bangcheng; Tan, Ji; Chen, Lan; Zhang, Haifeng; Ma, Xiaohan; Qiao, Yuqin; Liu, Xuanyong
Abstract: The recurrence of bone tumors in the early stage and poor osseointegration in the late stage are the main challenges in the clinical treatment of osteosarcoma. Thus, developing a bone implant with time-ordered anti-tumor and osteogenic abilities may be a promising strategy for osteosarcoma therapy. Here, we constructed a NIR and H2 O2 dual-responsive Zr-MOF film composed of Zr ions and ferrocene on the titanium and then loaded the anti-tumor drug doxorubicin (DOX) by electrostatic interaction. Under the stimulation of H2 O2 in the tumor microenvironment, the Fe 2+ in this Zr-MOF film transformed to Fe 3+, which could reduce the negative charge of the Zr-MOF to release DOX. Besides, this drug-loading Zr-MOF film possessed good photothermal conversion capability, which enabled the rapid synthetic anti-tumor effect of chemotherapy and photothermal therapy in the initial stage by using NIR irradiation. In vitro results confirmed that the drug-loading Zr-MOF film exhibited good anti-tumor performance against two kinds of human osteosarcoma cells (Saos-2 and 143B cells), which could be further enhanced by using NIR irradiation, and it also showed good anti-tumor properties in vivo . On the other hand, this Zr-MOF film became super hydrophilic after tumor treatment and then promoted the adhesion and the expression of osteogenic genes (ALP, Col-I, TGF-β, and Runx2) of bone cells. This study provides new sight into the design of bone implants with time-ordered tumor therapy and bone regeneration abilities in practical clinical applications. Highlights: A H2 O2 and NIR dual-responsive DOX-loaded Zr-MOF film was constructed on titanium. This Zr-MOF film possess time-ordered anti-tumor and osteogenic properties. A good anti-tumor effect was achieved under the synthetic photothermal/chemo-therapy. This Zr-MOF film became hydrophilic after treating tumor to enhance bone formation.